Geochemical characteristics and organic matter accumulation mechanism of the Permian Shanxi Formation transitional shale, eastern Ordos Basin: implications for paleo-weathering, provenance and tectonic setting - Zhuang, Hongzhan; Jiang, Yuqiang; Li, Xingtao; Jiang, Chan; Li, Shuxin; Wang, Zhanlei (Frontiers in Earth Science, 2025)
The transitional shale of the Permian Shanxi Formation is an important source rock for shale gas, tight sandstone gas, and coalbed methane in the Ordos Basin. This study takes third Sub-Member of Shanxi Formation as an example, and uses continuously collected shale core samples and matching geochemical data to restore the paleo-environmental conditions of its depositional period, clarify the formation mechanism of organic rich shale in different sedimentary environments under transitional facies background. According to different types of cross-plot patterns, paleo-weathering, provenance sources, and tectonic backgrounds were determined in this study. The results indicate that Shanxi organic-rich shale can be divided into two categories: estuarine shale in Unit 1 and lagoon shale in Units 2–4. The average TOC value of estuarine shale is significantly higher than that of lagoon shale, reaching 5.55%. Estuarine shale is mainly deposited in an suboxic-anoxic bottom water environments, with high surface seawater productivity, which is conducive to the formation and preservation of a large amount of organic matter. Lagoon shale is mainly composed of Type II2 and III kerogen, with a weakly oxic bottom water environment and low water surface paleo-productivity. The organic matter mainly comes from terrigenous plant debris, and its high sedimentation rate can effectively accumulate and preserve it. The chemical weathering indicators of Shanxi transitional shale are controlled by sedimentary recycling, hydrodynamic sorting, and diagenetic alteration, and the influence of changes in the source area is relatively small. The Shanxi transitional shale is mainly deposited on the active continental margin under collision background, and its source is mainly granodiorite from the Qinling orogenic belt.